Situation Report: Albania, 12 February 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Albania to Establish Diplomatic Relations with Morocco Albania Trade Delegation to Leave for UAR Albanian-Soviet Evenings "Zeri i Popullit" Supports French Communists Albanian Trade Delegation to Ghana Albanian Leaders Accused of Nepotism